Weak Humanism and the Economic Mission of English Education. Issue 1 (2nd January 2018) - Collin, Ross
Abstract: This article examines a theory of 'weak humanism' that says (1) secondary English classes should focus on personal development and culture and (2) English classes should deliver economic benefits indirectly, i.e. as knock-on effects of studying the personal and the cultural. Economic benefits are defined here as knowledge/skills students may use to improve their economic positions. This theory of weak humanism emerged as a popular idea among 140 professors of English education surveyed by the author and a colleague. Building out from previous analyses of the survey results, the present article reads weak humanism against a backdrop of shifting economic systems. Weak humanism is shown to take some of its current form in opposition to a regime of high-stakes standardised testing that integrates English education into a system of surveillance capitalism. The article concludes with a call for English teachers to resist surveillance capitalism by taking a revolutionary humanist tack to the work of English education.